Representing the Life Course of a Nineteenth-Century Aquatic Entertainer Through Different Modes of Expression - Day, Dave (Repertório, 2020)
The nineteenth-century development of swimming for women was stimulated by the public appearances of professional female natationists who performed in endurance events, exhibited and raced in swimming baths, and displayed ornamental swimming skills in music hall tanks, aquaria and circuses. These aquatic promotions were significant features in the Victorian sporting and entertainment landscape and by the end of the century, working class ‘naiads’ and ‘mermaids’ were performing before all social classes. This paper explores the practices of these women through the life course of Agnes Beckwith, the leading female natationist of the period who appeared throughout the United Kingdom, Europe and America, where her performances stimulated several imitators. This paper diverges from previous scholarly work on Agnes, characterised by its traditional empiricism, in adopting two different modes of expression, an archival-based biography and a creative writing piece scripted in the form of a dialogue between Agnes and her father. This fictional exchange covers the period between 1875, when Agnes undertook her first public endurance swim in the Thames, and her father’s death in 1898. In taking this approach the authors are making tentative steps towards experimentation in historical writing and exploring the different ways in which sporting biography might be represented. The hope is that other sports historians might take up the challenge of thinking more creatively about the ways that their work might be reproduced so that the field of sport history can be further developed.